Crystal structure of dimethyl 4,4′-oxydibenzoate, C16H14O5 - Maxweel Lindley; Cárdenas Alejandro; Brito Iván (Zeitschrift für Kristallographie - New Crystal Structures, 2018)
C16H14O5, Aba2 (no. 41), a = 7.4156(5) Å, b = 31.415(2) Å, c = 5.9451(4) Å, V = 1384.98(16) Å3, Z = 4, Rgt(F) = 0.0316, wRref(F2) = 0.0924, T = 297(2) K.